ATTITUDE OF SECONDARY SCHOOL TEACHERS TOWARDS INCLUSIVE EDUCATION - Singh, Ranjeet; Jain, Vinod Kumar; Yadav, Shivani (International Journal of Research -GRANTHAALAYAH, 2025)
Inclusive education aims to ensure the participation of all students, regardless of their abilities or disabilities, in mainstream education systems. Teachers play a pivotal role in implementing inclusive practices.. Inclusive education is a crucial aspect of educational equity, and understanding teachers' perspectives is essential for effective policy implementation. This study explores the attitudes of secondary school teachers towards inclusive education, with a focus on how these attitudes vary based on geographic location and gender. Inclusive education, which promotes the integration of all learners—regardless of abilities or backgrounds into mainstream classrooms, relies heavily on the perspectives and readiness of teachers to implement inclusive practices. The research investigates whether differences exist in the attitudes of rural and urban teachers, as well as between male and female educators. Findings reveal that there is a noticeable difference in attitudes based on location, with urban teachers generally demonstrating more favorable views toward inclusive education compared to their rural counterparts. Although this difference is evident, it is moderate in strength and not consistently significant at more stringent levels of analysis, indicating that while place of service may influence teacher attitudes, it is not the sole determining factor. In contrast, gender differences in attitudes toward inclusive education are more pronounced and consistent. Female teachers exhibit a significantly more positive outlook on inclusive education than male teachers. This suggests that gender plays a substantial role in shaping perceptions and openness toward inclusive teaching practices. The study highlights the importance of addressing these attitudinal differences through targeted professional development, training programs, and institutional support. Encouraging positive attitudes among all teachers regardless of their background or gender is essential for the successful implementation of inclusive education. The findings offer valuable insights for policymakers, educators, and stakeholders aiming to foster inclusive learning environments in secondary schools.